DMAIC METHODS FOR CANS CRUSHED PROBLEM SOLLUTION IN A MILK POWDER INDUSTRY - Rêgo, S. da S.; Syed, W. A. P.; Prates, G. A. (Revista Brasileira de Engenharia de Biossistemas, 2015)
Problems with rusty cans, crushed or stewed, can lead to diseases like Botulism due to contain bacteria that cause foodborne illness. This study was conducted at the milk powder company in São Paulo State, Brazil. On every segment, the milk powder is packed, mostly by aluminum cans are internally coated with varnishes and other materials to protect the metal milk taste-taken over from aluminum. Therefore, the study aim was to solve the problem of cans crushed that for both methodology was used as a case study with a quantitative approach through the DMAIC method developed by Six SGMA. It conducted a observation on disposal cans at the company verifying an average loss and, from that historic data, calculated a loss of goal. A target set was calculated the annual saving project. During the application of DMAIC, it was found that the loss highest rate were occurring in transport cans between the factory and the factory that fills milk. Several actions were taken to address problems that resulted in dented cans and in the first two months of control phase, there was lower losses than the calculated goal, resulting in savings. It was noted that the transport between the two plants is still affecting the discard canisters.